Réponses

2013-04-25T20:49:47+02:00

a) 2(x+1) = 3(x-1)

     2x+2 = 3x-3

     2x-3x = -3-2

     -x = -5

      x = 5

 

b) 3(2-3y) = -(y-2)

     6-9y = -y+2

     -9y+y = 2-6

     -8y = -4

      y = 4/8 = 1/2

 

C) -2(a-1) = 4(2a+1)

     -2a+2 = 8a+4

     -2a-8a = 4-2

     -10a = 2

       a = 2/-10 = -1/5

2013-04-25T20:56:47+02:00

2(x+1) = 3(x-1)

2x+2 = 3x-3

2x-3x = -3-2

-x = -5

 

3(2-3y) = - (y-2)

6 -9y = -y+2

-9y +y = 2-6

-8y = -4

y = 4/8 = 1/2

 

-2(a-1) = 4 (2a+1)

= -2a+2 =8a+4

= -2a-8a = 4-2

-10a = 2

a = -2/10 = -1/5